Analisis Sikap Belajar Siswa dalam Memahami Mata Pelajaran IPS Kelas VII di MTs Al Huda Bandung - Firda Aulia; Jani Jani (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2024)
Student learning attitudes are one of the factors that influence the learning process and student learning outcomes. From the results of these observations, researchers found several research focuses, namely 1). What is the student's learning attitude in understanding the Integrated Social Sciences subject material for class VII at MTs Al Huda Bandung 2). What are the factors that influence students' learning attitudes in understanding social studies subjects in class VII at MTs Al Huda Bandung, 3). How do teachers act in appreciating positive student learning attitudes and overcoming negative student learning attitudes in understanding social studies subjects for class VII at MTs Al Huda Bandung? This research is a type of qualitative research using a case study approach. Data collection tools through observation, interviews and documentation. The results of this research indicate that the learning attitudes of class VII students at MTs Al Huda Bandung have positive learning attitudes and negative learning attitudes. There are two factors that influence the learning attitudes of class VII students at MTs Al Huda Bandung, namely internal factors (from within the student) and external factors (from outside the student). The teacher's action in appreciating the learning attitudes of class VII students at MTs Al Huda Bandung is to give praise, additional marks and prizes, while to overcome negative learning attitudes, namely by giving advice or punishment.